Fundamental solution in elasto-thermodiffusive (ETNP) semiconductor materials - Kumar, R.; Kansal, T. (Archives of Mechanics, 2015)
In this paper, the fundamental solution of system of differential equations in the theory of elasto-thermodiffusive(ETNP) semiconductor materials in case of steady oscillations in terms of elementary functions is constructed. Some basic properties of the fundamental solution are also established.